Discoblock‐Associated Subarachnoid Hemorrhage: A Case Report - Sonbol, Ahmed M.; Ewais, Abdel Fattah; Kassab, Farid; Khalid, Khalid Mohammed Ali; Mohammed, Mohammed Awad A.; Ali, Hassan Sirajaldeen Alhassan; Elgack, Mohammed M. (Case reports in neurological medicine, 2025)
The discoblock procedure entails the administration of an anesthetic agent during discography to pinpoint the origin of spinal pain in challenging diagnostic scenarios. Known for its minimal complication rate, the most frequently documented adverse effect is discitis. This case report introduces a novel observation of subarachnoid hemorrhage following a discoblock procedure. Initially presenting with persistent lower back pain, the patient exhibited dehydrated lumbar discs on imaging, characterized by altered T2 signal intensity and a diffuse disc bulge impacting the anterior thecal sac at the L4‐5 level, alongside degenerative scoliosis at L2‐3. These findings suggested the potential origins of symptoms at L4‐5 or L2‐3, leading to the decision to proceed with L4‐5 discoblock. Symptom alleviation postdiscoblock, coupled with prophylactic cefazolin administration, indicated the necessity for further management at the L4‐5 disc level. Subsequently, the patient presented with status epilepticus 9 hours later, with brain magnetic resonance imaging revealing anomalous hyperintensities in the left temporoparietal sulci and the left ambient cistern, prompting suspicion of subarachnoid hemorrhage. This study elucidates the procedural indications for discoblock, explores potential factors contributing to complications, and delves into the safety considerations surrounding this intervention.